Release of Stage 2 of Havelock North Drinking-Water Inquiry - Editors (New Zealand Science Review, 2017)
​Stage 2 of the Inquiry into Havelock North Drinking-Water has been released by the Department of Internal Affairs. Stage 1, which addressed the causes of the water contamination incident and assessed the conduct of those responsible for providing safe drinking water in Havelock North, had been released in May 2017.The Inquiry was set up in September 2016, following the widespread outbreak of gastroenteritis in Havelock North in August 2016, with more than 5000 people falling ill.